General equilibrium effects of public adaptation in agriculture in LDCs: Evidence from Ethiopia - Amsalu W. Yalew; Georg Hirte; Hermann Lotze-Campen; Stefan Tscharaktschiew (Technische Universität Dresden, Center of Public and International Economics (CEPIE), 2017)
Ethiopia is one of the most vulnerable countries to climate change. This is because its important economic sector, agriculture, is virtually rain-fed. The role of the sector in the current economic structure and the potency of the anticipated biophysical impacts of climate change necessitates proactive adaptation in agriculture. This, however, breeds questions of adaptation costs and adaptation finance. This study attempts to derive plausible range of planned adaptation costs in agriculture along with their economy-wide and regional effects in Ethiopia. It also assess the economy-wide and regional effects of the likely options available to a government of a least-developed country to finance adaptation in agriculture. The results show that planned public adaptation in agriculture puts pressure on government surplus, impedes on manufacturing and private services, and GDP of urbanized regions. As such, it may strain the current macroeconomic endeavors of the country which puts government driven structural transformation and reducing fiscal deficit relative to GDP at the center. Government of Ethiopia may reconcile this by laying out incentives to urban agriculture and private investment in agriculture. Besides, foreign support in the form of biotechnology transfer and debt-relief may help to control the side effects of grants on foreign exchange market and trade balance.
urn:nbn:de:bsz:14-qucosa-227316
Keywords: C68; D58; H50; H60; O55; Q16; Q28; Q54; Q56; Q58; R11; R13; 330; climate change; agriculture; public adaptation; CGE model; Ethiopia